Gendered patterns of work and time use: A review of methods and innovations - Chakraborty, Ananya; Ravula, Padmaja; Seymour, Greg; Slavchevska, Vanya (CGIAR GENDER Impact Platform, 2021)
This review paper presents a collection of tools and methodologies for understanding/studying gendered work patterns and time use, with a focus on agriculture and allied activities. In addition to scoping the literature for methods, it also offers new methodological insights into gendered dimensions of rural work and time use to support data-collection efforts. Rural women’s work is often uncounted or underestimated in traditional laborforce surveys because of the multiplicity of activities they engage in throughout the year and their infrequent, short-term and informal nature. However, accurate, consistent, and comparable data on the work, employment and time use for women and men is imperative to track progress on global goals for gender equality and guide development interventions. We discuss qualitative and quantitative methods, tools and innovative approaches to collect data on work and time use in rural areas, along with an in-depth discussion on methodological issues that can guide further research to strengthen accurate and reliable data-collection efforts. This review is not only a ‘one-stop shop’ for different methods and tools related to studying work patterns, labor and time use; it also offers researchers and development practitioners opportunities for conducting more focused research towards developing new and innovative tools, and gives some clues about how to better move forward to achieve gender equality and equity goals. This can occur through better and more nuanced data to understand and analyze work patterns and time use in different contexts, geographies and sociocultural environments.